Antioxidative Constituents of Centella Asiatica L. Urban - Yusuf, Norhayati (2011)
Antioxidants present in fruits and vegetables are well known to contribute to the defense mechanisms against oxidative stress. Centella asiatica, locally known as pegaga is claimed to have high antioxidant as well as medicinal properties. In spite of extensive studies made on the triterpenes production associated with the healing properties of this plant, the protective natural antioxidative constituents have rarely been studied. The influence of the medium composition and physical factors on the production of antioxidant activity has not been reported. Thus, this study was carried out to determine the antioxidative constituents and antioxidative properties of twelve accessions of C. asiatica intact plants as well as callus cultures in response to treatment with 0, 10, 25 and 50 μM of paraquat (PQ) for five days. Apart from that, the production of α-tocopherol, ascorbic acid and carotenoid content were also studied by manipulating the biochemical and physical culture growth conditions. Results obtained from the studies revealed that the antioxidative constituents of C. asiatica intact plants and cultures vary significantly between the accessions. Accession CA03 exhibited the highest concentrations of ascorbic acid and glutathione while CA10 produced the highest concentration of α-tocopherol and carotenoid. The antioxidants studied were also successfully detected in cultures of C. asiatica with CA08 callus being most dominant in ascorbic acid and α-tocopherol, while CA12 callus was highest in carotenoid content; no significant differences were observed in the glutathione content of the calluses. The amounts of the non-enzymatic antioxidants were significantly higher in cell cultures compared to the leaf tissues except for carotenoid content. Specific activities of superoxide dismutase (SOD), catalase (CAT) and glutathione reductase (GR) were high in CA03, but they had lower ascorbate peroxidase (APX) specific activity. On the other hand, large variation was observed in the specific activities of the antioxidative enzymes in callus cultures with CA09 showing higher specific activities of SOD and CAT while CA01 and CA11 demonstrated higher activities of GR. Moreover, the APX specific activity was found to be higher in CA02 and CA08 compared to other accessions. CAT, GR and APX specific activities were found to be higher in callus cultures while contrasting results were observed for SOD. Assays on total antioxidants, scavenging effect on 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals and superoxide radicals showed that both C. asiatica intact leaves and calluses possessed lower activities compared to control. In contrast, almost all leaf accessions showed excellent scavenging effect on hydroxyl radicals compared to the calluses. In response to PQ treatment, the leaf chlorophyll content decreased subsequently with the progress of necrosis. Hydrogen peroxide in CA03 leaf and callus were significantly induced at early phase of treatment and further decreased at the end of experiment, while PQ treatment had no significant effect on the level of malondialdehyde (MDA) and electrolyte leakage. Contrasting patterns were observed in other accessions. Furthermore, the viability and growth of cell cultures decreased significantly with increased PQ concentrations and time of exposure. The above results indicated that CA03 was the most robust accession and considered as a tolerant accession. Further studies on the effect of PQ on the antioxidants using CA03 concluded that oxidative stress caused by PQ triggered the production of α-tocopherol and carotenoid content as well as CAT and GR specific activities while significantly lowered the production of ascorbic acid and APX specific activity. Manipulating the physical and biochemical culture conditions managed to produce higher concentrations of ascorbic acid, α-tocopherol and carotenoid content of C. asiatica calluses. Further studies concluded that combination of 3.0 mg/l 2,4-Dichlorophenoxyacetic acid (2,4-D) with 1.0 mg/l kinetin was found to be the best plant growth regulator (PGR) combination for inducing ascorbic acid, α-tocopherol and carotenoid productions. Studies on the effect of medium composition revealed that full strength MS medium with 30-40 g/l sucrose, with addition of 0.5 to 1.0 g/l casein hydrolysate was the most favorable medium composition in enhancing the productions of all antioxidants studied. Varying the pH of the medium from 5.1 to 5.9 did not significantly affect the antioxidants produced. Higher light intensities with continuous illumination increased the production of ascorbic acid and α-tocopherol while calluses incubated in dark condition were able to trigger carotenoid production. The above results indicated that the antioxidants produced can be modulated by manipulating the medium composition, PGR combination and environmental conditions in in vitro cultures of C. asiatica.